In vitro assessment of P‐gp and BCRP transporter‐mediated drug–drug interactions of riociguat with direct oral anticoagulants. (28th August 2019) - Jacqueroux, Elodie; Mercier, Clément; Margelidon‐Cozzolino, Victor; Hodin, Sophie; Bertoletti, Laurent; Delavenne, Xavier
Abstract: As an alternative to vitamin K antagonists (VKAs), direct oral anticoagulants (DOACs) are increasingly prescribed in combination with riociguat in the treatment of chronic thromboembolic pulmonary hypertension (CTEPH). Pharmacokinetics of riociguat and DOACs are influenced by efflux transporters, such as P‐glycoprotein (P‐gp) and Breast Cancer Resistance Protein (BCRP). This work aimed to assess P‐gp and BCRP‐mediated drug–drug interactions of riociguat with DOACs using in vitro models. Bidirectional permeabilities of apixaban and rivaroxaban were investigated across MDCK‐MDR1 and MDCK‐BCRP models, in the absence and in the presence of increasing concentrations of riociguat (0.5–100 μm ). Calculated efflux ratios were subsequently used to determine riociguat inhibition percentages and half maximal inhibitory concentration (IC50). P‐gp–mediated efflux of apixaban and rivaroxaban was inhibited by 8% and 21%, respectively, in the presence of 100 μm riociguat. BCRP‐mediated transport of apixaban and rivaroxaban was inhibited by 36% and 77%, respectively. IC50s of riociguat on MDCK‐MDR1 and MDCK‐BCRP models were higher than 100 μm for apixaban and higher than 100 μm and 46.5 μm for rivaroxaban, respectively. This work showed an in vitro inhibition of BCRP‐mediated DOACs transport by riociguat. In vivo studies may be required to determine the clinical relevance of these transporter‐mediated interactions.